Codeine dependence:two case reports - Öztürk, Z.; Karakuş, G.; Evlice, Y. E. (Journal of Dependence, 2008)
Substance abuse is one of the most serious problems of our time. The problem affects not only the individual using the substance but also their families, cultural values, economics, and legal systems in society. Codeine, an opium derivative, is widely used among young people. This situation is clearly closely linked to the over-the-counter sale of codeine-containing medications. This report presents two cases of codeine addiction. Our first case is a 24-year-old male university student who was inpatiently treated in our clinic three times with the diagnosis of "substance addiction - codeine addiction." Our second case is a 29-year-old male university student who was inpatiently treated in our clinic with the diagnosis of "substance addiction - codeine addiction." It is crucial that the relevant authorities strictly regulate drugs containing addictive substances, especially opium derivatives, and prevent their over-the-counter sale.